Cure characteristics and vulcanizate properties of natural rubber/ground tyre rubber blends - Joseph, A.M; Salbi, K.B; Madhusoodanan, K.N; George, B (Rubber Science, 36(1): 2023. 109-118.)
This paper presents the potential of blending ground tyre rubber (GTR) with natural rubber (NR) as a strategy to address the management of end-of-life tyres. The present work also investigated the possibility of improvements with respect to vulcanizate properties of NR/GTR blends through two protocols viz. mechanical devulcanization of GTR before blending and incorporation of carbon black filler in the blends. The cure characteristics, crosslink density and vulcanizate properties of blends were determined and compared. Results showed that incorporating mechanically devulcanized GTR (DGTR) led to better vulcanizate properties compared to vulcanizates containing an equivalent amount of GTR. Additionally, low loading of carbon black filler improved the properties for both types of blends. The study suggests that the vulcanizate properties of virgin NR/GTR blends can be tailored to meet specific requirements by modifying the incorporation protocols. For meeting high tensile properties, the incorporation of mechanically devulcanized GTR is recommended, while for lower property requirements, GTR with a small amount of carbon black is recommended.
Keywords: Crosslink density; Crosslink scission; Devulcanization; Re-vulcanization; Rubber blends